ANALISIS PENGARUH PENGELUARAN PEMERINTAH BIDANG INFRASTRUKTUR, PENDIDIKAN DAN KESEHATAN TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT KABUPATEN/KOTA DI PULAU KALIMANTAN PERIODE 2009-2013 - B01111083, Damayanti Ferbina (Jurnal Pembangunan dan Pemerataan, 2015)
Purpose of this research is to analyzed the influence of government expenditure in infrastructure, education and health to economic growth and social welfare. The independent variable used are government expenditure in infrastructure, education and health, while the dependent variable is economic growth and social welfare. The results of this research are government expenditure in infrastructure and education influenced significant and positive on economic growth of 0,234 and 0,552, mean if government expenditure in infrastructure and education rose 1%, goverment expenditure rose 0,234% and 0,552%. While governmentÂ  expenditure in health influenced is not significant and negative on economic growth of -0,021, mean if goverment expenditure in health rose 1%, economic growth down 0,021%. Government expenditure in infrastructure and economic growth influence significant and positive to social welfare of 0,592 dan 0,267 mean if government expenditure in infrastructure and economic growth rose 1%, social welfare rose 0,592% dan 0,267%, while government expenditure in edication and health influence is not significant and negative to social welfare of -0,0196 dan -0,0325 mean, if government expenditure in education and health rose 1%, social welfare down 0,0196% dan 0,0325% Keyword : economic growth, government expenditure, social welfare,